Crisis as processes of change and opportunities (Revista Puertorriqueña de Psicologia, 2021)
The year of 2020 surprised us with one of the deepest crises that humanity can experience, a pandemic, the Coronavirus (COVID-19). In just months, life, as it was seen up to that point, took a turn diametrically opposite to what was our sense of “normality.” Things that until that moment we assumed as given and secure became fragile and uncertain. It has been a year of losses, gains, as well as analysis and rethinking of how we live and how we want to transform the crises that are experienced on a personal, professional, social, and/or global level. We continue learning that crises move us towards the collectivity, insofar as we live as subjects inserted and interconnected in the multiplicity of communities in which we identify ourselves. It is in and from them, where we can create new possibilities and, hopefully, better realities than the past. It is from a/this crisis and a pause that I assume with enthusiasm and a deep sense of commitment and responsibility, the editorial direction of the Puerto Rican Journal of Psychology of the Puerto Rico Psychology Association.I begin this new phase of the Puerto Rican Journal of Psychology with a special issue dedicated to community social psychology and the work carried out as part of the Interamerican Congress of Psychology held in 2019 in Havana, Cuba. Thanks to the work of the guest editors who collaborated on this special issue: Prof. Maria Malena Lenta (Argentina), Prof. Sandra Estrada-Maldonado (Mexico), Dr. Rodrigo Cabrera-del Valle (Chile) and Prof. Gustavo Rigueiral (Argentina). Although it is very likely that the possibility of experiencing a pandemic was not contemplated during the gestation of this project, these works are more relevant at times when we affirm that crises, such as a pandemic, can only overcome if working with a common objective, for and by those who make up our communities. I hope that these works allow us to continue reflecting on new ways to build better realities that are more fair and equitable for all. I want to acknowledge that the last Editorial Board led by Dr. Guillermo Bernal originated this special issue. I thank and congratulate the past Editorial Board for the dedication and work done for this journal over the past five years. In the same way, I want to acknowledge the important achievements made during those years by The Puerto Rican Journal of Psychology, such as the digitalization of all its volumes, important indexing and the glimpses of being indexed by the impact factor. A special thanks to Dr. Jennifer Morales Cruz for her collaboration and availability during the transition process.In this new phase of the Puerto Rican Journal of Psychology, I aim to work in four main areas: assessment, collaboration, visibility/dissemination and mentoring work. It is important, as Editor-in-Chief, to know the scope that our journal has achieved in the past 40 years and what the potential areas of growth are. This will be done through an evaluation process among colleagues and authors in order to identify areas to strengthen and develop. On the other hand, we will be strengthening collaboration within and outside our discipline. The complexity of realities that our society experiences requires a multidisciplinary and interdisciplinary perspective to be able to have a comprehensive vision of the subject of study, as well as to produce concrete proposals that respond to that level of complexity. Establishing collaborations with other disciplines will give us the opportunity to address the challenges that our society faces with a comprehensive perspective. Another area of importance is visibility and dissemination. Our Journal not only has a local reach but also in Latin America and the rest of the Caribbean. We want to continue expanding that visibility by focusing on the impact factor and the establishment of collaborations with translation programs that can assist us in the translation of those articles of greater relevance so that they can be accessible to non-Spanish speaking researchers. Finally, we want the journal to be able to contribute to a mentoring process for developing researchers and graduate students who need more assistance in translating their research work into publishable articles. There are many goals, illusions and a busy agenda for our Puerto Rican Journal of Psychology to continue documenting the knowledge of our discipline.This work cannot be done without the assistance of an editorial team. I welcome the Associate Editors, Dr. Mariluz Franco Ortiz, from the Interdisciplinary Research Institute of the University of Puerto Rico, Cayey; and Dr. Emily Sáez Santiago, from the Institute for Psychological Research of the University of Puerto Rico, Río Piedras. Both have a background in quantitative and qualitative research, which can guarantee that our development of knowledge is sensitive to the scopes and ways of studying at and explaining our subject of study. We will continue to count on the support of Prof. Marco Peña Jiménez, MSc from the University of Bordeaux in France, who for several years has been key personnel of the development of our Open Journal System platform. Prof. Peña Jiménez will be our System Manager. In this new phase, we have the position of Editorial Assistant. This position has been possible thanks to the support of the Puerto Rico Psychology Association. For this position, we have hired Mariely Vélez Pérez, MS, a doctoral student from the Department of Psychology at the University of Puerto Rico, Mayagüez. I appreciate the commitment that this new Editorial Board has assumed to give continuity to the legacy of our predecessors who built this space for the dissemination of the research works that account for our discipline, not only in Puerto Rico, but in Latin America, the rest of the Caribbean and beyond. Together we assume this task from a learning place, with enthusiasm and a deep sense of responsibility and with the purpose of ensuring an excellent work for our profession. I hope that you will join us in this new phase of this Journal and enjoy this Special Issue: Community Psychology: Discussions, Contributions and Challenges.Mae Lynn Reyes-Rodríguez, PhD., FAED Editor-in-chief Puerto Rican Journal of Psychology